(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Dictyospermum scale is the main scale pest in the citrus groves and also injures many ornamental plants on the Black Sea coast. Two to three generations of scales are developed yearly without winter diapause. Nymphal mortality in the winter is high, up to 78%. Fecundity is between 100 and 200 eggs per female. The enernies of Dictyospermum scale include six species of hymenopterous parasitoids, four predators, and also mites and spiders. Sixteen species of fungi were recorded from the scale: Trichotecium roseum Link is among the most common. The Aphelinidae parasitoids are Aphytis aonidiae Mercet, A. chrysomphali Mercet, A. mytilaspidis Le Baron, Encarsia citrina (Grow), E. aurantii (Howard), and E. fasciata (Malenotti) and the predators are Chilocorus renipustulatus Scriba, C. bipustulatus L., Exochomus quadripustulatus L., and Rhizobius lophantae Blais. (Coleoptera, Coccinellidae). The significance of entomophagous insects in controlling the pest was studied. Natural enemies may considerably lirnit the presence of Dictyospermum scale, but they do not appear to be capable of eradicating it. Sometimes the use of additional control measures is necessary.